THE EFFECTIVENESS OF THE USE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF CONTROL AND MEASUREMENT MATERIALS FOR FUTURE COMPUTER SCIENCE TEACHERS - Kenesbayev, С.М.; Mazhibayeva, Г.П. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
In modern education, digital technologies play an important role in the creation and management of control and measuring materials (CMM). In particular, the use of digital technologies in the development of CMM for future computer science teachers makes it possible to transform assessment methods and train future teachers more effectively. This article is devoted to the study of the effectiveness of the use of digital technologies in the development of control and measurement materials. The study involved 22 students of the Kazakh National Women's Pedagogical University, studying under the 4th year educational program "Informatics" and 26 faculty members of this institute. The authors interviewed students and teachers to explore the methods and tools used to effectively evaluate student learning in the form of Google as a data collection tool. A quantitative analysis was carried out based on the results of the survey. The questionnaire asked questions on modules such as teaching and learning methods, knowledge and skills assessment, feedback, technical resources and equipment. The study shows the need to train teachers in the effective use of digital technologies in the educational process. A general conclusion has been formed that the use of digital technologies in the training of future computer science teachers will lead to an increase in the quality of knowledge, adapt to modern requirements and will contribute to the formation of necessary skills among students.